Time and Temporalities in (Adult) Education and Learning - Sabine Schmidt-Lauff (Universidade de Lisboa, 2023)
With the modern era, time is radically rethought as an expression of movements under the aspect of its use and formability. Due to modern ideas of the nature of time as something socio-culturally changeable and individually responsible, time is no longer something objectively given, but a highly ambivalent and complex element of shaping. As such an element of creating, ordering, and controlling, time and temporalities are a fundamental part of lifelong and lifewide learning. All these observations make it clear how important the tracing and understanding of the effects of time on education and learning is and how unavoidable temporal-relational contextualization are. This special edition, consisting of seven articles, might illustrate how differentiated time-related approaches in education research and empirical exploration are evolving. This collection of articles presents theoretical conceptualizations, methodological approaches, epistemological models, and empirical inquiries about time and temporal phenomena highly relevant to education and learning.